2022
DOI: 10.3389/fcell.2022.901652
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric Potential in Next-Generation Organoids: Electrical Stimulation to Enhance 3D Structures of the Central Nervous System

Abstract: Pluripotent stem cell-derived organoid models of the central nervous system represent one of the most exciting areas in in vitro tissue engineering. Classically, organoids of the brain, retina and spinal cord have been generated via recapitulation of in vivo developmental cues, including biochemical and biomechanical. However, a lesser studied cue, bioelectricity, has been shown to regulate central nervous system development and function. In particular, electrical stimulation of neural cells has generated some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 251 publications
(438 reference statements)
0
4
0
Order By: Relevance
“…Although we demonstrate the integration of sensors within the cyborg islet platform, we anticipate that future advancements in this direction will enable multimodal characterizations, such as metabolite and oxygen sensing 50 . Leveraging the recently demonstrated ability of electrical stimulation to promote maturation of stem cell-derived organoids 51,52 will in turn enable feedback control, such as tunable electrical or chemical stimulation 50 . Thus, we expect that future progress in multifunctional stretchable mesh nanoelectronics will allow for closed-loop sensing and actuation, offering a powerful approach to further improve organoid function.…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrate the integration of sensors within the cyborg islet platform, we anticipate that future advancements in this direction will enable multimodal characterizations, such as metabolite and oxygen sensing 50 . Leveraging the recently demonstrated ability of electrical stimulation to promote maturation of stem cell-derived organoids 51,52 will in turn enable feedback control, such as tunable electrical or chemical stimulation 50 . Thus, we expect that future progress in multifunctional stretchable mesh nanoelectronics will allow for closed-loop sensing and actuation, offering a powerful approach to further improve organoid function.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models are used to study RP associated with splicing factors by knock-in or knockout gene editing [ 32 ]. However, in addition to ethical concerns, none of the rodent models are fully representative of the onset and development of human retinal diseases due to genetic and clinical diversity [ 33 , 34 , 35 ]. For example, photoreceptors and RPE cells are the primary degenerated cells for RP, but it has been reported that splicing factors-associated animal models developed late-onset functional deficiencies in mutant RPE, while a nearly normal phenotype of photoreceptor cells was observed [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 201 In addition, custom-built devices could be developed to better approximate specific physiological scenarios or to accommodate the requirements of NIs with bespoke formats. 202 However, experimental findings from in vitro ES studies remain poorly translatable, which is due in part to the lack of standardised set-ups and protocols. To address this limitation, computational in silico models have been explored to enhance the reproducibility of ES protocols and streamline clinical translation.…”
Section: Considerations For Biohybrid Ni Fabricationmentioning
confidence: 99%